Synthesis and preliminary gas permeation properties of vitreous composite clinoptilolite membranes. Issue 5 (4th May 2022) - Kennedy, D. A.; Mujčin, M.; Omar, T.; Tezel, F. H.
Abstract: In this study, we communicate our initial findings regarding the development of novel inorganic composite clinoptilolite membranes. The membranes were formed from natural clinoptilolite microparticles sintered together using specialty glass atop a porous Al2 O3 porous disk that was used as a support. Fourier transform infrared spectroscopy and x-ray diffraction analysis was used to confirm that the natural clinoptilolite used in this study maintains its overall structural conformation following heat treatment as high as 1073 K. Surface and cross-sectional scanning electron microscopy imagery of the prepared membranes showed the formation of a porous clinoptilolite – glass composite layer and a mostly glass layer with lesser porosity. Single gas He, CO2, CH4, and N2 permeation experiments were carried out to evaluate the initial performance parameters of the membranes. Single gas membrane permeation decreased with increasing amount of glass, and ranged from 2 × 10 −7 mol/m 2 s Pa for the membrane prepared with 30 wt. % clinoptilolite as filler to as high as 4 × 10 −6 mol/m 2 s Pa for the 50 wt. % clinoptilolite membrane. The ideal selectivity was calculated from the single gas permeance for potential natural gas or biogas CH4 /N2 and CO2 /CH4 separations. These values were the highest at 1.7 ± 0.2 and 1.9 ± 0.1 for the membranes prepared with 40 wt. % and 30 wt. % clinoptilolite, respectively. Considerable refinements to this technique are necessary in order to minimize the presence defects before it may be used as an alternative to inorganic membranes or mixed matrix membranes as an approach when zeolite crystallization is difficult to achieve.